Online Shopping Transformation: The Impact of Virtual Events on Brands - Roel Hangsing; Gianina Amanda Azahra; Prida Ariani Ambar Astuti; Antonius Widi Herdianto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Tokopedia needs an effective communication strategy to establish a strong and positive brand image. One of their efforts towards this is to create a brand experience through the virtual event of the Tokopedia WIB TV Show. This study aimed to analyze the impact of brand experience on Tokopedia’s brand image through this virtual event on YouTube. The study also aimed to identify the key indicators of brand experience, namely sensorial, emotional, intellectual, and behavioral, which have the most important influence on brand image. This study used a quantitative approach and survey research methods, and the analysis was based on the theory of the communication persuasion matrix. The findings showed a strong correlation between brand experience through the virtual Tokopedia WIB TV Show on YouTube and Tokopedia’s brand image. Furthermore, it was observed that an increase in brand experience has led to a positive increase in brand image. The four indicators of brand experience are integral to influencing brand image and cannot be viewed as separate entities.